Pengaruh Transfer Pricing dan Intangible Asset Terhadap Penghindaran Pajak (Tax Avoidance) - Arraufah Ristianti; Dani Ramdani (GLOBAL SCIENTS PUBLISHER, 2026)
The phenomenon of tax avoidance is gaining increasing attention because it harms developing countries more than developed countries. Cases of transfer pricing and tax compliance at large manufacturing companies, such as PT Perusahaan Gas Negara and PT Aneka Tambang, demonstrate that this practice remains widespread and has a significant impact on state revenues. This study was conducted to determine the effect of transfer pricing (X1) and intangible assets (X2) on tax avoidance (Y) in manufacturing companies in the basic materials sector listed on the Indonesia Stock Exchange in 2020-2024. The research population is in the form of financial statements from manufacturing companies in the basic materials sector from 2020 to 2024. The use of the research population was in the form of 9 companies as a sample according to the criteria in purposive sampling. The researcher used panel data regression analysis techniques. The results of the study show that partial transfer pricing has a significant effect on tax avoidance and assets do not partially have no effect on tax avoidance. However, transfer pricing and intangible assets simultaneously affect tax avoidance. The correlation coefficient value shows that 16.31% of the variation in tax avoidance can be explained by independent variables, while the remaining 83.69% is influenced by other variables that are not included in the research model.